DETERMINANT OF GOOD CORPORATE GOVERNANCE AND FREE CASH FLOW EFFECT ON EARNING MANAGEMENT - Miswaty; Stasia, Anna (KRISNA: Kumpulan Riset Akuntansi, 2023)
The purpose of this study was to determine the effect of the size of the audit committee, the proportion of independent commissioners, institutional ownership, managerial ownership, and free cash flow either simultaneously or partially on earnings management. The data used are sources that already exist, both internal and external data and the data can be accessed via the internet and information publications. The data used is the financial statements of manufacturing companies for the 2018-2020 period. The data analysis method used multiple linear regression. The results showed that Institutional Ownership had a significant positive effect on Earnings Management, Free Cash Flow had a negative effect on Earnings Management. Meanwhile, the size of the audit committee, the proportion of independent commissioners, and managerial ownership have no effect on earnings management